Interreligious Dialogue: An Islamic Approach - Elius, Mohammad; Khan, Issa; Mohd Nor, Mohd Roslan (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2019)
Dialogue among the followers of different religions is a necessary condition for promoting peace, tolerance, harmony, and religious co-existence in today’s world. Islam is a religion of peace, tolerance, unity, justice, love and brotherhood which always fosters mutual, cooperative and positive relation between one another irrespective of caste, creed and religion for the greater happiness of mankind. The purpose of this study is to examine the concept of interreligious dialogue and its relation to Islam. It highlights the importance of interreligious dialogue in Islam as a model for strengthening mutual respect, understanding, cooperation and human dignity. The study is followed by textual analysis and historical interpretation of the Qur’an and Sunnah. This study also includes the treatment of Muslim rulers to the people of other religions with a view to understand the real picture of interreligious relationship in any Islamic society. The research shows how Islam plays a unique role in promoting interreligious dialogue and harmony through accepting all previous prophets as the prophets of Islam and granting the freedom of religious practices by the people of any religion, culture and civilization. Finally, the research also provides some important suggestions to future research in this area more effectively which will resolve many interreligious conflicts and establish better understanding among the people of various religions around the world.